Dashboard for Monitoring Financial Performance of Business Islamic Boarding School Sukorejo Situbondo - Achmad; Nanda Hidayansono (Jurnal Informasi dan Teknologi, 2024)
Every company must have a good strategy. A strategy built from the results of company performance analysis. One aspect that needs to be controlled and evaluated was financial performance. From financial performance analysis, management may find out the strengths and weaknesses from the financial side. So it can be used to improve company strategy. By automating financial ratios and presenting information graphically and up to date. So, management can find out developments in company performance in real time in supporting economic decision. This research aims to produce a dashboard for monitoring the financial performance of PP Salafiyah Syafi'iyah Sukorejo Situbondo. The data obtained consisted of primary and secondary sources, which were collected using observation, interviews, documentation and questionnaires. Then its validity was tested using triangulation methods, extended observations, and discussions with colleagues. Qualitative data was analyzed using the approach of Miles and Huberman. Meanwhile, in developing information systems, the waterfall model is used. The conclusion reached was the availability of a Dashboard for Monitoring the Financial Performance of the Sukorejo Islamic Boarding School Business. The system presents information about turnover development, business results or profits, and financial position, in graphical and quantitative form. The system also provided information about the health level of each business entity and business unit.